Pelatihan Pembuatan Keset dari Pakaian Bekas Guna Meningkatkan Ketrampilan Ibu PKK di Dusun Gumelem Desa Banjarejo Kecamatan Kedungpring Lamongan - Siti Musarofah; Mesra Surya Ariefin; Bayu Malikhul Askha; Arian Yusuf Wicaksono; Muhammad David (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
Based on observations that have been made while there, that many people there do not use used clothes that are not used anymore and even they throw them away and burn them. From this statement, the community service team this time held a training on making used doormats to reduce waste from used clothes that are no longer used. Making doormats from used clothing waste aims to reduce waste and add new skills and knowledge for PKK mothers. This activity lasts for 2 days on Monday and Tuesday, December 19 – 20, 2022. Located in Banjarejo village hall. And followed by 23 PKK mothers. The training succeeded in making PKK mothers get solutions as well as benefits and new knowledge related to the processing of used clothing waste.